Konsep dan Metode Tadabbur dalam Al-Qur'an - Zamroni Ishaq; Ihsan Maulana Hamid (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2021)
his study tries to focus on answering important questions related to the concept of tadabbur in the Koran?. By using the istinbat method as well as seeing and exploring the texts of the previous Muslim heritage (turath) it is hoped that later it will be known how what methods and means can be used as material to understand the meaning of the Koran through tadabbur. This research is included in the category of library research. The purpose of this study seeks to present a method that can be used for readers and reviewers of the Koran so that it can be easy through the tadabbur method, explore the deepest meaning of the contents of the Koran, take the knowledge and wisdom in it, and then apply it in everyday life. The research begins by explaining the meaning of tadabbur and sentences that have similar meanings to it, such as the words tafsir, tadhakkur, tafakkur, istinbat . Then proceed with explaining the urgency of tadabbur, law, conditions, division, faidah, mentioning things that can help and hinder in tadabbur. This is followed by a description of how to perform tadabbur in the Koran. And to further conclude by mentioning method errors that often occur in the process of etiquette.